A Qualitative Exploration of a Worksite Wellness Mini-Grant Program. (April 2019) - Warehime, Shane; Coyle, Brian; Abel, Kayla; Sedani, Ami; Holes, Justin; Dinkel, Danae
Mini-grant programs are an increasingly popular method for outside organizations (eg, non-profits, state agencies) to support wellness initiatives. However, little is known about mini-grant programs in worksites. The present study explored the implementation and outcomes of a worksite wellness mini-grant program. Semi-structured interviews were conducted with 12 wellness champions representing 12 worksites that were involved in a mini-grant program over a 4-year span. Interviews focused on general use, barriers and facilitators, and outcomes of the mini-grant initiatives. Mini-grants were generally used to support a short-term activity, such as purchasing food, which was not allowed per grant funding, or supporting a one-time event—this type of use diverged from recommended use of funds. Participants reported that outcomes from the mini-grant initiates were largely positive, highlighting culture shifts and increased awareness/perception of employer support for wellness. Barriers included culture (eg, employee attitudes, motivation), environment (eg, infrastructure, weather), and worksite characteristics (eg, multiple locations, number of employees), while facilitators included employee interest and involvement, established wellness culture, awareness and accessibility (eg, providing options, education), and support (eg, employer support, support from outside organizations). There was overlap between certain barriers and facilitators, indicating key areas of focus for future research and mini-grant programs.